Percutaneous Nephrolithotomy is Safe and Efficient when Performed on Early Adolescents with Adult-Sized Tools - Rajab Ali, Wajahat Aziz, Amanullah Memon, Ubedullah Shaikh, (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To report our experience of percutaneous nephtrolithotomy using adult size instruments in young adolescents. Study design: Retrospective case series Place and duration of study: Department of Urology, Isra University Hospital Hyderabad between 1st January 2006 and December 2016, Methodology: Twenty five adolescents underwent percutaneous nephrolithotomy were enrolled. The records of patients between the ages of 10 and 15 years underwent percutaneous nephtrolithotomy at our institute was examined. The percutaneous nephtrolithotomy was performed using a 24-Frnephroscope. Stone burden and location were reviewed. Stone clearance was reviewed after the surgery. Renal units with ≤4mm residual stone on postoperative imaging were considered stone free. Results: Mean age of patients was 12±2 yrs. Extracorporeal Shockwave Lithotomy (ESWL) was required in 4 patients and one patient had retrograde intrarenal surgery (RIRS) for residual stones. The total percentage of stones removed was 84% (21/25). One patient in our group had factor VII deficiency, another had a kidney with a horseshoe shape, and a third had post-pyelolithotomy residual stones. Three patients needed blood transfusions, and one patient experienced transitory urine leakage for more than 12 hours. There were no complications that required medical or surgical attention. Conclusion: Percutaneous nephrolithotomy in young adolescents is safe and effective. Adult size instruments can be used safely for percutaneous nephtrolithromy in this group of patients. Keywords: Percutaneous nephrolithotomy (PCNL), Adolescents, Nephrolithiasis